1968
DOI: 10.21236/ad0771740
|View full text |Cite
|
Sign up to set email alerts
|

A Computer-Directed System for Measuring Distance between Edges in Optical Images

Abstract: An automatic measuring system lor time-varying optical images is described. After the operator specifies the location of the segment to be measured on an outline image produced by the system, the equipment periodically prints the current length on a teletype. A detailed study of optical edge detection by two different transformations is given. Finally tests of the system as a means of measuring and recording dynamic blood vessel diameters in the ra! mesentery are explained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0

Year Published

1977
1977
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 7 publications
(1 reference statement)
0
61
0
Order By: Relevance
“…Validity estimates using reading CBMs yielded correlation coefficients ranging from .43 to .86. A validity comparison with the AIMSweb© Maze (Shinn & Shinn, 2002) produced a median estimate of .55 for third grade (Hilton-Prillhart, 2011). In addition, a stepwise regression analysis showed that AIMSweb© Maze did not significantly increase the MIR:R’s prediction ( R 2 = .37) of Star Reading Scores (Advantage Learning Systems, 1997).…”
Section: Methodsmentioning
confidence: 99%
“…Validity estimates using reading CBMs yielded correlation coefficients ranging from .43 to .86. A validity comparison with the AIMSweb© Maze (Shinn & Shinn, 2002) produced a median estimate of .55 for third grade (Hilton-Prillhart, 2011). In addition, a stepwise regression analysis showed that AIMSweb© Maze did not significantly increase the MIR:R’s prediction ( R 2 = .37) of Star Reading Scores (Advantage Learning Systems, 1997).…”
Section: Methodsmentioning
confidence: 99%
“…Maze scores were obtained from administration of AIMSweb maze. AIMSweb maze was administered by teachers following a standardized format for “Older Students and Students Familiar with Maze Directions” as outlined in the AIMSweb Training Workbook (Shinn & Shinn, 2002b, p. 16). The maze assessment was administered in a large group setting, typically during reading class.…”
Section: Methodsmentioning
confidence: 99%
“…Both AIMSweb measures, ORF and maze, have established convincing, direct evidence of technical adequacy as progress-monitoring tools (Gersten, Compton, Connor, Dimino, Santoro, Linan-Thompson, & Tilly, 2009). However, it should be noted that the early reliability and validity studies of AIMSweb maze were conducted at the lower grades, and none included a general population of eighth-grade students, the focus of this study (Shinn & Shinn, 2002a, 2002b) More recently, the test–retest reliability of AIMSweb maze in a middle-grade sample were reported as .86 to .87 for the same passage, and .68 to .78 for different passages in Grade 8. Concurrent (.51–.69) and predictive validity (.51–.73) coefficients obtained from correlating maze scores with scores on norm-referenced measures of reading comprehension were also reported (Tolar et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study uses national longitudinal panel survey data to explore the process by which father involvement affects the development of gender. Hess, 1970; Kohn, 1969) or his "presence" or "absence" was the primary independent variable explaining outcomes in children ranging from achievement orientation, self-esteem, dating and sexual behavior, delinquent behavior, and gender identification (Biller, 1974;Shinn, 1978;Herzog and Sudia, 1973;Kinnaird and Gerrard, 1986;Kagel and Schilling, 1985). However, while taking into account the effects of father presence and the status that he confers on the family, 2 this research has failed to explore the actual behavior or involvement of fathers within the family.…”
Section: Paternal Involvement and The Development Of Gender Expectatimentioning
confidence: 99%